PENINGKATAN HASIL BELAJAR SISWA KELAS 4 PADA MATERI MAGNET DENGAN MODEL PEMBELAJARAN PROJECT BASE LEARNING - Siti Durrotul Yatimah; Endang Suprapti; Umi Arsiyati (Universitas Muhammadiyah Surabaya, 2024)
The improve student learning outcomes through a project based learning model. This research is classroom action research with two assessments. The research subjects were 4th grade students at SD Negeri Margorejo III /405 Surabaya, totaling 32 students. The data collection techniques are: observation, documentation and tests. The analysis technique is an interactive analysis model, which consists of four components of the analysis process in the form of data collection, data reduction, data presentation and drawing conclusions. The average value of the class before using the project based learning model, namely pre-action, was cycle I rose to 81, 25% and in cycle II it rose to 93, 75%. Based on the research results, it was concluded that there was an increase in the learning outcomes of fourth grade students at SDN Margorejo III/405 Surabaya. This increase in learning outcomes can be seen from the percentage of achievement of learning indicators which include oral communication, written communication and group communication. Therefore, the use of the project-model based learning can improve mastery of the concept of magnetic force and learning outcomes of grade 4 students at SD Negeri Margorejo III /405 Surabaya for the 2023/2024 academic year